Skin surveillance attitudes and behaviors in relation to skin checks for early signs of skin cancer in a sample of secondary school students and teachers in Palermo, Western Sicily (Italian Journal of Public Health, 2008)
Background: Malignant melanoma (MM) can be readily treated in its earliest stages: survival rate, whendetected early, is up to 95,0%. This justifies investigations on contributive factors and measures forprecocious detection of skin tumors to improve early detection and to increase survival rates. The purpose ofthis survey was to collect information about knowledge, attitudes and behaviors on prevention in relation toskin checks for early signs of skin cancer on a sample of secondary school students and teachers.Methods: A sample of secondary school students and teachers from Palermo, was recruited using the clustersampling method. A self-administered questionnaire, consisting of twenty four multiple choice questions wasused as the survey instrument. Statistical analysis of data obtained was performed using Openstat software.Results: The research showed a good level of awareness about skin cancer risk factors, which seemed to bestrictly correlated with age. On the contrary, practice of skin self-examination (SSE) is not as widespread, andonly 4,8% regularly checked the parts of their bodies most exposed to the risk of developing skin cancer. Bothstudents and teachers indicated that school-based health education programs are the best way to promotethe importance of prevention.Conclusions: In many countries mortality is not increasing at the same rate as incidence for MM. The practiceof SSE may play a vital role in improving early detection and survival rates. Therefore, school interventions topromote knowledge of the benefits of regular SSE should be implemented.
Keywords: skin self examination (SSE); skin cancer prevention; sun exposure